(untitled) - Reddi, Lakshmi N. (Hoboken, N.J., 2003)
Completely up to date with coverage of new developments in separators, filters, and geosynthetics, this textbook includes exercises in seepage quantification, seepage forces, and dewatering. Complete coverage is useful in all subdivisions of civil engineering. Material is divided into three modules:Principles and mathematical solutions, filters and drainage layers, applications. It serves as a useful reference for geotechnical, environmental, and structural engineers, hydrologists, geologists, agronomists, and soil scientists.
Keywords: Seepage,Groundwater flow,Sự thấm qua,Lưu lượng ngầm